2012
DOI: 10.1100/2012/973292
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Persistent Organochlorine Contaminants (PCDD, PCDF, and PCB) in Fish Collected from the Polish Baltic Fishing Areas

Abstract: Concentrations and congener-specific profiles of PCDDs, PCDFs, dl-PCBs, and ndl-PCBs were determined in five species of edible fish from the Baltic Sea (ICES 24–27): salmon (Salmo salar), Baltic herring (Clupea harengus membras), sprat (Sprattus sprattus balticus), sea trout (Salmo trutta m.trutta), and cod (Gadus morhua callarias). Marker PCBs were the dominant compounds (0.07–60.84 ng/g  w.w.), followed by dl-PCBs (0.64–6.07 pg WHO-TEQ/g w.w.) and PCDD/PCDFs (0.22–5.67 pg WHO-TEQ w.w). The concentration leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 12 publications
(22 reference statements)
2
12
1
1
Order By: Relevance
“…The trend of a declining cod population (G. morhua callarias) in the Baltic Sea over the last several decades has coincided with its increased contamination and leads us to assume that the cod population may be suffering from AhR-related effects. The assumption can be justified by the extremely high concentrations of PCDD/Fs and DL-PCBs that have been observed in the liver of this species (25,30). These can also be indicative of a contaminant burden in the gonads as maternal transfer of contaminants to gonads has been documented (5).…”
Section: Fig 2 Electronic Wastementioning
confidence: 99%
See 2 more Smart Citations
“…The trend of a declining cod population (G. morhua callarias) in the Baltic Sea over the last several decades has coincided with its increased contamination and leads us to assume that the cod population may be suffering from AhR-related effects. The assumption can be justified by the extremely high concentrations of PCDD/Fs and DL-PCBs that have been observed in the liver of this species (25,30). These can also be indicative of a contaminant burden in the gonads as maternal transfer of contaminants to gonads has been documented (5).…”
Section: Fig 2 Electronic Wastementioning
confidence: 99%
“…Most organohalogen contaminants released over the years are still present in the aqueous environment and thus are accessible to marine organisms. Elevated concentrations of PCDDs, PCDFs, and dl-PCBs in some Baltic fish species (salmon, herring, and sprat) have been shown in several surveys in European member states (18,25,30). Recently the contamination profiles of PBDDs and PBDFs were described in the tissue of Baltic wild salmon and compared with chlorinated dioxins, dibenzofurans, and PCBs.…”
Section: Fig 2 Electronic Wastementioning
confidence: 99%
See 1 more Smart Citation
“…on seasonal changes in lipid content connected with physiological cycles (e.g. reproduction), age, feeding habits and the environmental conditions [18,[20][21][22][23][24][25][26][27] have been investigating the impact of seasonal changes in the concentrations of halogenated organic compounds in the Baltic salmon, due to the spawning run phenomenon, which remains insufficiently recognized.…”
Section: Sample Processing and Analysismentioning
confidence: 99%
“…Poland, after signing the Stockholm Convention, is obliged to report data on annual emissions of pollutants, including POPs. Nevertheless, majority of the research has been carried out on food and fish samples [11][12][13]. The results obtained by Lizak et al [14] using high resolution gas chromatography / high resolution mass spectrometry (HRGC/HRMS) showed that of 78 samples of examined foodstuffs, in 18 cases concentrations of toxic compounds exceeded acceptable limits [15].…”
Section: Introductionmentioning
confidence: 99%